2015
DOI: 10.3892/etm.2015.2194
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of matrix metalloproteinase-1 in the maternal umbilical serum, trophoblasts and decidua leads to preeclampsia

Abstract: The aim of the present study was to explore the levels of matrix metalloproteinase-1 (MMP-1) and tissue inhibitor of metalloproteinase-1 (TIMP-1) in the maternal umbilical serum, placenta and decidua of patients with preeclampsia compared with those in normotensive pregnant females. A total of 73 pregnant females were recruited as the test subjects, including 43 inpatients with hypertensive disorders in pregnancy and 30 normal pregnant females as the control. The 43 inpatients with hypertensive disorders in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 16 publications
2
28
1
Order By: Relevance
“…Measurements of TIMP-1 and -2 in the circulation and umbilical serum have shown increases or no change in PE versus Norm-Preg women (Montagnana et al, 2009; Deng et al, 2015; Eleuterio et al, 2015), while other studies have shown increases in TIMP-1 and -3 in PE patients (Zhu et al, 2014). The role of MMPs and TIMPs in modulating vascular function and the endothelial dysfunction associated with PE should be further examined in future studies.…”
Section: Placental Ischemia As An Initiating Event In Preeclampsiamentioning
confidence: 91%
See 1 more Smart Citation
“…Measurements of TIMP-1 and -2 in the circulation and umbilical serum have shown increases or no change in PE versus Norm-Preg women (Montagnana et al, 2009; Deng et al, 2015; Eleuterio et al, 2015), while other studies have shown increases in TIMP-1 and -3 in PE patients (Zhu et al, 2014). The role of MMPs and TIMPs in modulating vascular function and the endothelial dysfunction associated with PE should be further examined in future studies.…”
Section: Placental Ischemia As An Initiating Event In Preeclampsiamentioning
confidence: 91%
“…MMP-1 is also expressed in cytotrophoblasts and syncytiotrophoblasts of the placenta and decidua and may play a role in trophoblast invasion. MMP-1 levels in the umbilical cord blood, placenta and decidua are lower in PE than Norm-Preg women, and the low levels of MMP-1 are in a positive correlation with the severity of the disease (Deng et al, 2015). …”
Section: Placental Ischemia As An Initiating Event In Preeclampsiamentioning
confidence: 99%
“…Also, TIMPs are important endogenous modulators of MMPs activity [16, 18, 25, 88, 89]. Some studies have shown increases or no change in TIMP-1 and −2 in the circulation and umbilical cord serum of preeclamptic vs normal Preg women [16, 24, 90]. Other studies have shown increases in TIMP-1 and −3 in preeclamptic patients [91].…”
Section: Discussionmentioning
confidence: 99%
“…While preeclampsia has been linked to a decrease of MMP-1 expression in placenta, umbilical serum and decidua, choriocarcinoma has been linked to an increase expression of MMP-1 in extravillous trophoblast (Cohen et al, 2012;Deng et al, 2015;Vegh et al, 1999), suggesting that US28 MMP-1 phenotype may be more related to cell survival. In transfected HUVECs, detectable levels of MMP-1 and MMP-10 were recorded, consistent with previous data showing upregulation of these mRNA upon exposure to inflammatory stimuli (Montero et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…decidua have been associated with both normal and abnormal pregnancies (Deng et al, 2015;Lockwood et al, 2014;Vegh et al, 1999;Xu et al, 2000). Here, concentration of nine MMP in the cell culture supernatant were analysed in two in vitro settings by Luminex assays.…”
Section: (A) (B)mentioning
confidence: 99%